“You have become our dreaming”: AIDS and Queer Community in David Levithan’s Two Boys Kissing - Mizzian Galeote, Juan Jesús (My University, 2021)
This end-of-degree dissertation will address the topics of gay identity, American gay literature, AIDS narratives, LGBTQ+ young adult literature, and the idea of queer community in David Levithan´s Two Boys Kissing. The aim of this dissertation is to analyse Levithan’s book from an AIDS perspective, and from a LGBTQ+ young adult literature perspective, it will especially focus on the aspect of queer community within this latter subgenre. The dissertation aims to prove that Levithan’s book can be analysed from these two different perspectives, and that there is cultural gay identity
“Vosotros ahora sois nuestro sueño”: el SIDA y la comunidad queer en Dos chicos besándose, de David Levithan.
Keywords: Levithan, David -- Crítica e interpretación; Identidad sexual; Libros infantiles y juveniles; SIDA; Comunidad queer; Narrativa del SIDA; Literatura LGBTQ+; Literatura juvenil; Herencia cultural